2010
DOI: 10.1159/000314271
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Serotonin Content and Transpulmonary Platelet Serotonin Gradient in Patients with Pulmonary Hypertension

Abstract: Background: The serotonin system has repeatedly been associated with the pathogenesis of pulmonary hypertension (PH). Objective: To comparatively analyze plasmatic and intrathrombocytic serotonin levels in arterial and mixed venous blood of patients with PH and unaffected controls to elucidate pulmonary serotonin metabolisms. Patients and Methods: Catheters were placed in the radial and pulmonary artery in patients with PH (n = 13) for diagnosis and in age-matched controls (n = 6) undergoing percutaneous closu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…PH was grouped according to hemodynamics in modest [mean pulmonary artery pressure (mPAP) = 26-39 mm Hg], severe (mPAP ≥40) and very severe (mPAP ≥40 with mixed venous oxygen saturation <60%) [18]. Venous N-terminal pro-brain natriuretic peptide (NT-proBNP) was measured [19,20]. Sleep studies were performed as previously described [14].…”
Section: Methodsmentioning
confidence: 99%
“…PH was grouped according to hemodynamics in modest [mean pulmonary artery pressure (mPAP) = 26-39 mm Hg], severe (mPAP ≥40) and very severe (mPAP ≥40 with mixed venous oxygen saturation <60%) [18]. Venous N-terminal pro-brain natriuretic peptide (NT-proBNP) was measured [19,20]. Sleep studies were performed as previously described [14].…”
Section: Methodsmentioning
confidence: 99%
“…There is mounting evidence that serotonin is key to the development of PAH, as increases in plasma serotonin caused by the anorexigen, fenfluramine, markedly increased the chances of developing PAH, and in at least one study, increased serotonin transport was causally linked to smooth muscle cell hypertrophy [55,56]. More recently, a small study demonstrated a negative transpulmonary platelet serotonin gradient in PAH patients, while control subjects exhibited a positive gradient [57]. These data are suggestive that the lungs of PAH patients may take up serotonin from platelets or that altered hemodynamics in the lungs of PAH patients cause degranulation and release of serotonin into the blood.…”
Section: Inflammation and Platelet Activation In Pahmentioning
confidence: 99%
“…Hence, an altered function of these cells, especially of platelets, plays a pivotal role in the progression of PH [17]. By releasing coagulatory and inflammatory cytokines, activated platelets induce thromboembolic complications, which is a major cause of death in PH patients, but also enforce vasoconstriction and disease progression [18,19]. Accordingly, in the serum of patients with PH inflammatory and platelet activation markers such as sCD40L and sP-selection are elevated underlining our hypothesis of enhanced platelet activation in PH, which is in our study reflected by increased PMP levels [20,21].…”
Section: Pmps In Phmentioning
confidence: 99%